Schefflera beamanii - Damit, A.; Tsen, S.; Colin Ruzelion Maycock; Sugau, J.; Khoo, E.; Nilus, R.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Schefflera beamanii is restricted to Bukit Hampuan Forest Reserve, Sabah which is a Totally Protected Area (TPA). The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2 and not declining. Due to fire events within the reserve in the past, forest fire is a serious plausible threat to the species in the future. This event could drive the species towards Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Schefflera beamanii is endemic to Sabah, Malaysia. It is restricted to the Bukit Hampuan Forest Reserve.